PUBLIC TRUST AND DIGITAL GOVERNANCE: SOCIAL MEDIA SENTIMENT ON INDONESIA’S FREE NUTRITIOUS MEAL PROGRAM - Bayu Aulia Priyantomo; Suprayoga; Denny Iswanto (RADJA PUBLIKA, 2026)
This study examines public sentiment, communication governance, and policy implementation of Indonesia’s Free Nutritious Meal (MBG) program, focusing on Surabaya as a national pilot area. Using a mixed-method approach, the research combines social media sentiment analysis and qualitative interviews. A total of 476,859 social media conversations collected between February and March 2025 were analyzed using the BERT model. The findings show that 52.4% of responses were negative, 32.3% neutral, and 15.2% positive. Negative sentiments mainly relate to delayed wage payments, food safety concerns, and transparency issues, indicating communication gaps and declining public trust. Meanwhile, positive sentiments emphasize support for improving children’s nutrition, family welfare, and social equity. The implementation of MBG in Surabaya reflects a centralized yet participatory governance model. Coordination between the National Nutrition Agency (BGN) and local governments is essential but constrained by limited resources and uneven kitchen readiness. Schools and parents demonstrate strong support for the program. Additionally, the Simanis Application supports monitoring and evaluation, reflecting the adoption of digital governance principles that enhance transparency and accountability. Overall, effective communication, coordination, and community participation are crucial for strengthening public trust and ensuring the sustainability of the MBG program.